2020
DOI: 10.1007/s11356-020-10033-6
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton distribution characteristics and its relationship with bacterioplankton in Dianchi Lake

Abstract: Phytoplankton and bacterioplankton perform important ecological functions in lake ecosystem. In this paper, the abundance and composition of phytoplankton and bacterioplankton at 13 sites of Dianchi lake during the wet and dry seasons were monitored, and the relationship between phytoplankton and bacterioplankton in this plateau lake was studied. Phytoplankton community structure analysis was carried out by ocular method, and bacterioplankton was investigated by high-throughput 16S rRNA gene Illumina sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
(39 reference statements)
3
13
0
Order By: Relevance
“…This observation is consistent with one study from this reservoir, which did not separate FL and PA (Yue et al, 2021). Other studies on plateau lakes also reported the predominant role of Proteobacteria and Actinobacteria in the water column (Wu et al, 2019;Zhang et al, 2020). Both groups constitute frequent and highly abundant bacterial members in eutrophic lakes (Trusova and Gladyshev, 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation is consistent with one study from this reservoir, which did not separate FL and PA (Yue et al, 2021). Other studies on plateau lakes also reported the predominant role of Proteobacteria and Actinobacteria in the water column (Wu et al, 2019;Zhang et al, 2020). Both groups constitute frequent and highly abundant bacterial members in eutrophic lakes (Trusova and Gladyshev, 2002).…”
Section: Discussionsupporting
confidence: 91%
“…Only a few studies reported the bacterial community structure in the Yungui-Plateau region, and they rarely separated the FL and PA fractions. Zhang et al (2020) investigated the relationship between phytoplankton and bacterioplankton in Dianchi Lake, which was mainly dominated by Proteobacteria and Bacteroidetes. Wu et al (2019) studied the vertical profile of the sediment bacterial community in Lake Lugu and suggested that chemical variables were the main drivers of dominant phyla.…”
Section: Introductionmentioning
confidence: 99%
“…The initial cell density used in this study has been reached in some coastal areas (Dursun and Tas 2019 ) and in lake ecosystems (Zhang et al 2020a , b ). Lower phytoplankton abundances commonly observed in coastal waters (Effendi et al 2016 ; Fehling et al 2012 ) could intensify the toxic effects of Cu exposition (Moreno-Garrido et al 2000 ; Singh and Shrivastava 2016 ) affecting the physiological processes of coastal marine organisms and their communities (Leal et al 2018 ; Trombetta et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The following 10 amino acids were examined in the cells: Glu, His, Met, Arg, Asp, Lys, Pro, Val, Ile, and Phe. They were selected because of their antioxidant properties (Hwang et al 2019 ) and their role in the response of plants to several types of abiotic stress (Marquis et al 2020 ; Zhang et al 2020a , b ).…”
Section: Methodsmentioning
confidence: 99%
“…The phytoplankton compositions of Dianchi Lake were partially consistent with that of previous studies, including the dominant cyanobacteria taxon ( Microcystis ) and the dominant eukaryotic phytoplankton taxa ( Stephanodiscus , Ceratium sp. and Cryptomonas among others; Feng et al, 2020; Wang et al, 2016; Zhang et al, 2021; Zhang, Zuo, et al, 2020). And most of the predominant phytoplankton taxa (e.g., Microcystis , Navicula and Cyclotella ) in the inflow rivers were the same as the historical monitoring results, but there were still some differences.…”
Section: Discussionmentioning
confidence: 99%